Interfaith Inheritance within Muslim Families in Indonesia: Practices, Philosophical Foundations, and Prospects for the Development of National Inheritance Law - Fahimah, Iim; Suwarjin, Suwarjin; Gusmansyah, Wery; Zubaedi, Zubaedi; Jayusman, Jayusman (Universitas Islam Negeri Jakarta, 2024)
This article examines the mechanisms of inheritance resolution in cases of different religions in several regions of Indonesia, namely North Sumatera, Central Java, Bengkulu, and East Java, focusing on integrating customary law, religious law, and state law in inheritance distribution. This research employs a descriptive qualitative approach with a case study method, where data is gathered through interviews, observations, and literature reviews on the practice of inheritance among families with different religions. The findings reveal that family deliberation remains the primary principle in resolving inheritance disputes despite the religious differences among heirs. Social and cultural values such as kinship, mutual assistance, and interfaith tolerance play a significant role in the inheritance process, with each region having its own ways of accommodating religious differences within families. The legal pluralism approach, which combines customary law, religious law, and state law, forms the foundation for developing a fair and inclusive national inheritance law. This article suggests strengthening the principle of deliberation, creating an adaptive legal unification, and formulating inclusive regulations for interfaith inheritance rights to create a harmonious and just inheritance system that aligns with the spirit of Indonesia's cultural diversity. AbstrakArtikel ini mengkaji mekanisme penyelesaian waris beda agama di beberapa wilayah di Indonesia, yaitu Sumatera Utara, Jawa Tengah, Bengkulu, dan Jawa Timur, dengan fokus pada integrasi hukum adat, agama, dan negara dalam pembagian warisan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus, di mana data diperoleh melalui wawancara, observasi, dan kajian literatur mengenai praktik waris beda agama dalam masyarakat. Hasil penelitian menunjukkan bahwa meskipun terdapat perbedaan agama di antara ahli waris, musyawarah keluarga menjadi prinsip utama dalam penyelesaian sengketa waris. Nilai sosial dan budaya seperti kekeluargaan, gotong royong, dan toleransi antaragama berperan penting dalam proses pembagian warisan, dengan setiap daerah memiliki cara-cara tersendiri dalam mengakomodasi perbedaan agama dalam keluarga. Pendekatan pluralisme hukum yang memadukan hukum adat, agama, dan negara menjadi landasan dalam pengembangan hukum waris nasional yang adil dan inklusif. Artikel ini menyarankan penguatan prinsip musyawarah, unifikasi hukum yang adaptif, serta penyusunan aturan inklusif untuk hak waris lintas agama, guna menciptakan sistem kewarisan yang harmonis dan adil sesuai dengan semangat keragaman budaya Indonesia.